PELAKSANAAN PERJANJIAN KERJA SAMA PENGELOLAAN MAHAKAM LAMPION GARDEN KOTA SAMARINDA - Jessi Aprilia Wulandari; Purwanto; Amsari Damanik (Yuriska: Jurnal Ilmiah Hukum, 2025)
Background : The purpose of this research is to determine the implementation of obligations by the Samarinda City Government and PT. Samaco, as well as the certainty of PT. Samaco's completion of its contribution payment obligations to the Samarinda City Government, based on the cooperation agreement for the management of Mahakam Lampion Garden in Samarinda City. Research Metodes: The research method used in the study of the implementation of the cooperation agreement for managing Mahakam Lampion Garden in Samarinda City employs a socio-legal research approach. Findings: The obligations of the Samarinda City Government have not been fully implemented, especially related to the performance of the PMU which has not been satisfactory in responding to the development of the Mahakam Lantern Park area. Likewise, PT. Samaco has not fully implemented its obligations, especially regarding the payment of contributions. Furthermore, the payment of contributions by PT. Samaco to the City Government for the 2016-2018 period has been completed through a monthly installment scheme. Meanwhile, for the 2020-2021 period, there has been no certainty from the Samarinda City Government regarding the request to eliminate contributions due to force majeure. Conclusion : The Samarinda City Government must make an addendum together with PT. Samaco regarding the cooperation agreement to further clarify the obligations of the parties in the cooperation agreement because the initial agreement did not provide adequate legal certainty, so that it became a factor causing several obligations not to be fully implemented.